1990
DOI: 10.1002/hc.520010611
|View full text |Cite
|
Sign up to set email alerts
|

Samarium (II) diiodide‐induced reductive cleavage of SeSe and TeTe bond in diphenyl diselenide and ditelluride leading to a samarium phenylselenolate and tellurolate: Preparation of unsymmetrical alkylphenyl selenides and tellurides

Abstract: Diphenyl diselenide and diphenyl ditelluride were reduced by samarium (11)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the course of studying reactions mediated by SmI 2 , we and others have noticed the negative impact of the quality of some batches of samarium metal on the efficiency of SmI 2 formation . In the worst cases, it has been noted that the preparation of SmI 2 using a batch of samarium metal might fail completely under standard conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of studying reactions mediated by SmI 2 , we and others have noticed the negative impact of the quality of some batches of samarium metal on the efficiency of SmI 2 formation . In the worst cases, it has been noted that the preparation of SmI 2 using a batch of samarium metal might fail completely under standard conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The above appearance showed that nitro groups and Se Se bonds were simultaneously reduced by SmI 2 . According to the literature [5,6], we considered that an intermediate 2 could be generated in situ during the reduction procedure. Then, many kinds of electrophilic reagents were tested to react with these species 2.…”
Section: Resultsmentioning
confidence: 99%
“…1. 20 We are grateful to the National Natural Science Foundation of China and Laboratory of Organometallic Chemistry, Shanghai Institute of Organic Chemistry, Chinese Academy of Sciences, for ®nancial support.…”
Section: Methodsmentioning
confidence: 99%